Role of heat shock factor-1 activation in the doxorubicin-induced heart failure in mice - Vedam, Kaushik (American Physiological Society, 2010)
Treating cancer patients with chemotherapeutics, such as doxorubicin (Dox), cause dilated cardiomyopathy and congestive heart failure because of oxidative stress. On the other hand, heat shock factor-1 (HSF-1), a transcription factor for heat shock proteins (Hsps), is also known to be activated in response to oxidative stress. However, the possible role of HSF-1 activation and the resultant Hsp25 in chemotherapeutic-induced heart failure has not been investigated. Using HSF-1 wild-type (HSF-1(+/+)) and knock-out (HSF-1(−/−)) mice, we tested the hypothesis that activation of HSF-1 plays a role in the development of Dox-induced heart failure. Higher levels of Hsp25 and its phosphorylated forms were found in the failing hearts of Dox-treated HSF-1(+/+) mice. More than twofold increase in Hsp25 mRNA level was found in Dox-treated hearts. Proteomic analysis showed that there is accumulation and aggregation of Hsp25 in Dox-treated failing hearts. Additionally, Hsp25 was found to coimmunoprecipitate with p53 and vice versa. Further studies indicated that the Dox-induced higher levels of Hsp25 transactivated p53 leading to higher levels of the pro-apoptotic protein Bax, but other p53-related proteins remained unaltered. Moreover, HSF-1(−/−) mice showed significantly reduced Dox-induced heart failure and higher survival rate, and there was no change in Bax upon treating with Dox in HSF-1(−/−) mice. From these results we propose a novel mechanism for Dox-induced heart failure: increased expression of Hsp25 because of oxidant-induced activation of HSF-1 transactivates p53 to increase Bax levels, which leads to heart failure.